The effect of macroeconomic variables towards Malaysia stock market price - Ahmad Sufian, Abdullah (2017)
The purpose of the study is to find the macroeconomic variables factors that can affect the Malaysia stock market price. This study used the time series data for the variables including stock market price (KLCI), inflation rate, exchange rate, money supply (M2) and unemployment rate. By using the multiple regressions analysis model the finding shows all macroeconomic variables are significantly influenced Malaysia stock market price (KLCI) including unemployment rate. Besides the macroeconomics factor like money supply, exchange rate and inflation rate, unemployment rate as a new variable been tested to know the impact towards stock market price. However based on the results from the regression analysis shows only money supply (M2) has the positive influences towards Malaysia stock market price